Integration of Education in Human Resource Development: Transformation of the Human Resource Management Paradigm - A. Aminullah Alam; A. Erni Ratna Dewi (PT. Anagata Sembagi Education, 2024)
Education integration in human resource development (HRD) has become a central issue in the modern context. This study aims to examine the role of education integration in human resource development and its impact on the transformation of the HRD management paradigm. The method used is a literature study. The results show that educational integration, through curriculum adjustment to industry needs and implementation of competency-based training programs, is able to improve the quality and competitiveness of human resources. In addition, collaboration between educational institutions and the industrial sector has proven effective in bridging the skills gap that exists in the labor market. The research revealed that innovations in teaching and learning methods, as well as the development of soft skills such as leadership, teamwork and problem-solving, contribute significantly to improving the quality of human resources. The paradigm shift in HRD management is also characterized by increased investment in continuing education and vocational training relevant to global market demands. The implications of this research emphasize the importance of a strategic approach to HR management that prioritizes education as the main foundation for creating an innovative, adaptive, and highly competitive workforce in the era of globalization and digitalization. Thus, education policies that are responsive to industrial dynamics and active participation from the private sector in the education and training process are key factors in creating a sustainable HR development ecosystem. This shows that the synergy between education and industry not only improves individual competencies but also drives overall economic growth.